2014
DOI: 10.1371/journal.pone.0105296
|View full text |Cite
|
Sign up to set email alerts
|

Treatment Evolution after COPD Diagnosis in the UK Primary Care Setting

Abstract: RationaleTo assess the treatment progression during the 24 months following a formal diagnosis of chronic obstructive pulmonary disease (COPD) in the UK primary care setting.MethodsA retrospective cohort of newly diagnosed COPD patients was identified in the Clinical Practice Research Datalink (CPRD) from 1/1/2008 until 31/12/2009. Maintenance therapy prescribed within the first 3 months of diagnosis and in the subsequent 3-month intervals for 24 months were analyzed. Treatment classes included long-acting β2-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
49
1
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(62 citation statements)
references
References 12 publications
(13 reference statements)
11
49
1
1
Order By: Relevance
“…In our study, it was observed that within 2 years of initiating treatment for COPD, ICS therapy was added to 43% of patients on LABA or LAMA monotherapy, despite the low rate of exacerbations. This may reflect inappropriate initiation of ICS as previously described and is in line with the findings from other studies 16,17…”
Section: Discussionsupporting
confidence: 92%
“…In our study, it was observed that within 2 years of initiating treatment for COPD, ICS therapy was added to 43% of patients on LABA or LAMA monotherapy, despite the low rate of exacerbations. This may reflect inappropriate initiation of ICS as previously described and is in line with the findings from other studies 16,17…”
Section: Discussionsupporting
confidence: 92%
“…The use of inhaled triple pharmacologic therapy by patients with chronic obstructive pulmonary disease (COPD) is common; a UK study found that after 2 years, 46% of patients initially prescribed a long-acting bronchodilator and 39% of those prescribed an inhaled corticosteroid (ICS)/long-acting β 2 -agonist (LABA) or ICS plus long-acting muscarinic antagonist (LAMA) progressed to triple therapy (1). In a US study, 25.5% of patients with COPD, who had received at least one LAMA, LABA, ICS, or phosphodiesterase-4 inhibitor, received triple therapy within 2 years of being diagnosed (2) 4 advanced, symptomatic COPD, who are at risk of exacerbations.…”
Section: Introductionmentioning
confidence: 99%
“…Программа Adelphi, ориенти-рованная на респираторные заболевания, пред-ставлявшая собой перекрестное исследование консультирования пациентов в странах Европы и в США, показала конфликт между текущей реальной практикой и рекомендациями глобальной инициа-тивы GOLD в редакции 2011 г., документируя тот факт, что значительная часть больных с низким риском продолжают получать ИГКС/ДДБА как от-дельно, так и в сочетании с ДДАХ [68]. Более того, ДДБА как монотерапию получал небольшой процент больных с ХОБЛ из групп А и В. Было показано, что в реальной жизни переключение с ДДАХ на ДДБА, а также шаг вниз от ИГКС/ДДБА к ДДБА или ДДАХ встречались нечасто [69], в этой связи интересно понять прогрессивное снижение интереса к разра-ботке новых ультра-ДДБА в качестве монотерапии.…”
Section: комментарии экспертовunclassified